Ultralow-Power and Secure S-Box Circuit Using FinFET Based ECRL Adiabatic Logic - Kaza, Srilakshmi; Tilak, A. V. N.; Srinivasa Rao, K. (Journal of Science and Technology, 2018)
Advanced Encryption Standard (AES) is the widely used technique in critical cyber security applications. In AES architecture S-box is the most important block. However, the power consumed by S-box is 75% of the total AES design. The S-box is also prone to Differential Power Analysis (DPA) attack which is one of the most threatening types of attacks in cryptographic systems. In this paper, a three-stage positive polarity Reed-Muller (PPRM) S-box is implemented with 45nm FinFET using Efficient Charge Recovery Logic (ECRL) to reduce power consumption. The simulation results indicate up to 66% power savings for FinFET based S-box as compared to CMOS design. Further, the FinFET ECRL 8-bit S-box circuit is evaluated for transitional energy fluctuations and peak current traces to compare its resistance against side-channel attacks. The lower energy variations and uniform current trace exhibit the improved security performance of the circuit to withstand DPA and Differential Electromagnetic Radiation Attacks (DEMA).